Structure, competition and policy in India’s seed and agricultural biotechnology industries - Spielman, David J.; Kolady, Deepthi Elizabeth; Cavalieri, Anthony J.; Rao, N. Chandrasekhara; International Maize and Wheat Improvement Center; International Food Policy Research Institute; International Livestock Research Institute; International Rice Research Institute; WorldFish (International Food Policy Research Institute, 2014)
This study1 examined current constraints to increased private sector investment in the seed and agricultural biotechnology (agbiotech) sectors in India, particularly in relation to rice, wheat and maize improvement. It examines the structures of these industries, their potential effects on competition and innovation, and the policies that may improve both industry performance and the delivery of new productivity-enhancing technologies to India’s cereal production systems.